Sekolah Adaptif: Strategi Membangun Budaya Organisasi yang Responsif terhadap Perubahan - Rendy Reza Abitama; Muhammad Abror Rahmat; Muhamad Subkhan; Denda Ginanjar (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
An adaptive school is characterized by its ability to accommodate and respond to the dynamics of both external and internal environments, such as technological advancements, changes in educational policies, and evolving student needs. This research explores how schools can develop a culture of organization that is responsive to change through adaptive approaches. The study aims to investigate effective strategies for creating a flexible and innovative school environment and how the implementation of these strategies can enhance a school’s capability to handle challenges and changes. Through a qualitative approach using case studies of schools that have successfully applied adaptive principles, findings indicate that an adaptive organizational culture can improve educational quality and increase stakeholder satisfaction. The research is intended to provide practical guidance for educational leaders in designing and implementing sustainable adaptive strategies.